Effects of Family Influences on the Patient Planning to Undergo Bariatric Surgery - Sloan, Kelsey (East Carolina University, 2018)
Background: Obesity is a health issue with more than one-third of adults in the United States being considered obese (Odgen, Carroll, Fryar, & Flegal, 2015). Obesity can cause serious health problems such as diabetes but having bariatric surgery can remit the condition. Despite the known benefits, some wait many years before deciding to have surgery (Roberson Neil, Pories & Rose, 2016). Since many rely on family for decision-making the purpose of this study was to determine what influence a patient’s family has on the decision to choose bariatric surgery. Methodology: For this qualitative descriptive study, a secondary analysis of previously collected de-identified interview data was conducted. There were 24 participants who were interviewed during an appointment at the bariatric surgery clinic where they decided to undergo bariatric surgery. Data Analysis: The researcher and the mentor read the transcripts literally, first to gain a flavor of the conversations and then to mark comments thought to be related to family influence on surgery decisions. After individual review, the two met to organize the data. Lastly, there was consensus and the themes finalized. Results: Four main themes of influence were identified. Participants were influenced by their desire to improve quality of life with their family and to be a role model for their children. One said, “I want to be there for my kids.” There was a prevalence of family/marital factors that could be positive or negative influences and were often described as a family member previously against, but now supporting surgery. Finally there was motivating influence from successful other contacts that had had bariatric surgery. Conclusion: There is a considerable difference in the number of obese patients who are eligible to undergo bariatric surgery and the number who actually undergo the surgery. For this sample, family could influence the decision to choose surgery when the patient wanted to improve quality of life, be a healthy example for children and when the family supported the patient, encouraging their success. The influence of others who had bariatric surgery was noted and should not be discounted. Including the family and significant others in the patient pre-operative counseling may be helpful and may aid the nurse’s ability to create an individualized care plan for the patient and their family.
Keywords: decision-making; bariatric surgery; family support; obesity; perioperative nursing